Who is in the room? : queer strategies for redefining the role of the theater director - O'Harra, Brooke, 1973- (London ; New York : Routledge, 2024)
"With this book, Brooke O'Harra takes up directing as an artistic practice in and of itself. Speaking beyond and against craft, O'Harra drives the art of directing forward. O'Harra investigates a series of important questions: How do we wrest our work from institutional imperatives of public building and culture building? How can an artist-driven discourse lead us toward the urgencies of artists and their publics in this moment? How do we "make" plays? How do we activate the relationships of making, whether between artists in the rehearsal room or between the production and the audience? Brooke addresses all aspects of the directorial process: reckoning with the script through dramaturgy, working within the rehearsal room, collaborating with other artists, as well as staging and production. This exploration will be of great interest to students and scholars in performance studies with a particular interest in directing"--
Essay one. I'm bleeding all over the place: queer auteur director card catalog -- Essay two. Brings us together and keeps us apart -- Essay three. Deep listening, or i can't tell you how to do that play -- Essay four. Who is Joan Littlewood? or the impossibility of the Auteur -- Essay five. Actors! let them be astonishing -- Essay six. The education of the director.
Keywords: Theater -- Production and direction; Gay theater; PERFORMING ARTS / Theater / General; PERFORMING ARTS / General; PERFORMING ARTS / Theater / History & Criticism